Forecasting the Anti-Rabies Vaccine Demand at Jawaharlal Medical College and Hospital, Ajmer, Rajasthan: A Comparative Analysis based on Time Series Model - Bedi, Renu; Verma, Narendra; Gautam, Kunal; Agiwal, Varun (Indian Journal of Community Health, 2021)
Background: In India, high mortality and morbidity rates of human rabies is observed. Hence, a structured surveillance system is yet to be put in place for public health discussion. At the tertiary care hospital and all public health centres, requirement of anti-rabies vaccine is needed in advance to predict the upcoming months coverage so that wastage of vaccine is minimum. Objective: To find a suitable model for forecasting the appropriate stock of anti-rabies vaccines to avoid shortage and over-supply at anti rabies clinic. Methods and Material: This was a record based cross sectional study, conducted at anti rabies clinic of Jawaharlal Nehru Medical College and Hospital, Ajmer. Data of used anti rabies vaccine was taken from immunization inventory during the period from 2017 to 2020. Time series analysis based on Holt-Winter and Box-Jenkins methods were carried out to predict the need of vaccine. Results: Study series was not stationary and stationarity was observed by taken difference in the observation between two consequent months. Residuals of the series were normally distributed and independent to each other. ARIMA(0, 1, 1) was the best model in comparison to Holt-Winter model for prediction because of low value of model selection criterion. The forecasted value for anti-rabies vaccine was done for the year 2021. Conclusions: The following study concluded that time series can be used as a tool to forecast anti-rabies vaccine coverage and will help the policy makers to formulate appropriate plans and strategies and improve the management of vaccination resources and inventory.